2001
DOI: 10.1111/j.1540-8183.2001.tb00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Closure of Atrial Septal Defects with the STARFlex Device: Early Results and Follow‐Up

Abstract: The STARFlex device seems to offer better results than the CardioSEAL, with significantly lower rates of residual shunts and arm fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 13 publications
1
36
0
Order By: Relevance
“…There were three different devices used in this study in which successful transcutaneous closure has been previously observed [2][3][4]: STARFLEX (NMT Medical Boston, MA, USA), a modified version of the CardioSEAL (CS) double umbrella device, which has the addition of a self centering mechanism; Helex (W.L. Gore & Associates Inc., Flagstaff, AZ, echocardiogram (TOE) where indicated, to evaluate the shunt and its surrounding rims as well as to look for any associated cardiac abnormalities.…”
Section: P Ercutaneous Transcatheter Atrial Septal Defect (Asd)mentioning
confidence: 96%
“…There were three different devices used in this study in which successful transcutaneous closure has been previously observed [2][3][4]: STARFLEX (NMT Medical Boston, MA, USA), a modified version of the CardioSEAL (CS) double umbrella device, which has the addition of a self centering mechanism; Helex (W.L. Gore & Associates Inc., Flagstaff, AZ, echocardiogram (TOE) where indicated, to evaluate the shunt and its surrounding rims as well as to look for any associated cardiac abnormalities.…”
Section: P Ercutaneous Transcatheter Atrial Septal Defect (Asd)mentioning
confidence: 96%
“…long sheath [17,18], monitored by fluoroscopy and intracardiac echocardiography (ICE). The device was soaked in a normal saline solution (5 min) to hydrate the collagen discs, which had been dehydrated for packaging and transport.…”
Section: The Proceduresmentioning
confidence: 99%
“…More contemporary devices for closure of interatrial communications have improved compared to older occluders. Advancements include a simpler deployment technique involving only venous access, higher complete closure rates, eradication of wire fractures, and reduction of device-related thrombus formation [2,7,11,12]. However, structural factors such as atrial septal aneurysms (ASA), a large discrepancy in thickness between septum primum and septum secundum, as well as long PFO tunnels may potentially lead to a mismatch between the individual anatomy and the technical design of the device.…”
Section: Introductionmentioning
confidence: 98%